Conceptual legal framework of financial legal responsibility for violating the legislation in the field of budget revenue execution. - Vdovichena, Lidiia (Visegrad journal on human rights, 2018)
The article is devoted to the study of the conceptual legal framework of financial legal responsibility for vio lating the legislation in the field of budget revenue execution. Attention is paid to financial legal responsibility as a special type of legal responsibility. It is argued that the concepts and features of the studied category have both theoretical and practical significance.
Keywords: financial legal responsibility; financial sanctions; budget process; budget violations